Impact of Ground Flaxseed on Methane Reduction and their Influence on Nutrient Digestibility In-vitro - Singh, Gurjinder; Singh, Gurpreet; Hundal, Jaspal Singh (International Journal of Bio-resource and Stress Management, 2025)
The current study was carried out during the period of October, 2018 to March, 2019 at the Department of Animal Nutrition, College of Veterinary Science, Guru Angad Dev Veterinary and Animal Sciences University, Ludhiana, Punjab, India to assess the effect of the Ground flaxseed supplemented at 0, 5, 10, 15 and 20% of TMR on DM basis on in-vitro gas output and fiber degradation. Regardless of the levels of ground flaxseed, the net gas production (NGP) in flaxseed supplemented groups (5–20% level) was lower than control. The partitioning factor (PF) of flaxseed supplemented groups was significantly greater in relation to reference group. The NDF digestibility remained unaffected at supplementation levels ranging from 5% to 15% flaxseed compared to the control. However, it dropped significantly (p<0.01) with flaxseed supplementation at the 20% level. Although, ME availability was not affected by flaxseed supplementation. Significantly (p<0.01) high levels of acetate were observed in control than flaxseed supplemented groups at 15% and 20% levels. Relative proportions of butyrate and fermentable carbon dioxide varied significantly at 5% and 15% levels of flaxseed supplementations. Regardless of the level of flaxseed, methane percent of NGP, methane 100 mg-1 DDM and methane 100 mg-1 DOM depicted a significant reduction (p<0.01) relative to the control. Ammonia nitrogen levels remained unchanged across all levels of flaxseed supplementation. In conclusion, flaxseed supplementation mitigated the methane production and improved the digestibility without affecting ME availability.